2019
DOI: 10.1177/0021828619845950
|View full text |Cite
|
Sign up to set email alerts
|

Occultation of Planets by the Moon in European Narrative Medieval Sources

Abstract: Existing research dealing with astronomical observations from medieval Europe have extensively covered topics such as solar and lunar eclipses and sightings of comets and meteors, but no compilation of occultations of planets by the Moon has been carried out, being the data scattered in different publications. The main cause for this is the small number of observations that have reached us, their limited use for calculation of parameters associated with the rotation of the Earth and the fact that between the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This record is mostly consistent with the multiple ΔT constraints over 454-554 in previous studies, as shown in Figure 9. Generally, these ΔT constraints are located below the M + 21 ΔT spline curve, as shown in the Chinese occultation records of 516 (2893 s < ΔT < 5246 s) and 522 (3568 s < ΔT < 5090 s) in Sôma & Tanikawa (2016) and the Merovingian occultation record of 554 (3000 s < ΔT < 5500 s) in Martínez Usó & Marco Castillo (2019). Our ΔT constraint is also consistent with that of a Chinese report on a partial solar eclipse in 494, which identified a ΔT margin of ΔT < 5980 s and 6600 s < ΔT.…”
Section: Summary and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This record is mostly consistent with the multiple ΔT constraints over 454-554 in previous studies, as shown in Figure 9. Generally, these ΔT constraints are located below the M + 21 ΔT spline curve, as shown in the Chinese occultation records of 516 (2893 s < ΔT < 5246 s) and 522 (3568 s < ΔT < 5090 s) in Sôma & Tanikawa (2016) and the Merovingian occultation record of 554 (3000 s < ΔT < 5500 s) in Martínez Usó & Marco Castillo (2019). Our ΔT constraint is also consistent with that of a Chinese report on a partial solar eclipse in 494, which identified a ΔT margin of ΔT < 5980 s and 6600 s < ΔT.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…Likewise, existing ΔT reconstructions interpolated their spline curves based on only a small number of records. Inevitably, they accommodate large uncertainties owing in part to the scarcity of actual observational data (Stephenson et al 2016(Stephenson et al , 2018Morrison et al 2021) and have been subjected to regular updates with historical eclipse records with some occasional aids from historical occultation reports (Sôma & Tanikawa 2015;Martínez Usó et al 2016;Sôma & Tanikawa 2016;Gonzalez 2017Gonzalez , 2019Stephenson et al 2018;Martínez Usó & Marco Castillo 2019;Morrison et al 2021). It is also important to consider probable record provenance and probable observational sites and admit their geographical uncertainty, as they occasionally leave significant uncertainty in constraining probable ΔT margins in the historical period.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Other medieval planetary observations in the Latin West: While the RFA for A.D. 807 mentioned "Jupiter," lunar-planetary conjunction records for ±4 centuries around A.D. 807 did not name any planets. 60 A presumable Saturn occultation record in A.D. 806 by Ado 61 was actually our Jupiter occultation 807 Jan 30/31. The next known conjunction report with the planet name is found in A.D. 1283 (Parma, Italy).…”
Section: Jupiter Occultation By the Moon On Ad 807 January 30/31mentioning
confidence: 92%